MS4A4A: a novel cell surface marker for M2 macrophages and plasma cells. Issue 7 (11th April 2017) - Sanyal, Ratna; Polyak, Maria J; Zuccolo, Jonathan; Puri, Mandip; Deng, Lili; Roberts, Luc; Zuba, Ania; Storek, Jan; Luider, Joanne M; Sundberg, Ellen M; Mansoor, Adnan; Baigorri, Eva; et al.
Abstract : MS4A4A is a member of the membrane‐spanning, four domain family, subfamily A (MS4A) that includes CD20 (MS4A1), FcRβ (MS4A2) and Htm4 (MS4A3). Like the first three members of this family, transcription of MS4A4A appears to be limited to hematopoietic cells. To evaluate expression of the MS4A4A protein in hematopoietic cell lineages and subsets we generated monoclonal antibodies against extracellular epitopes for use in flow cytometry. In human peripheral blood we found that MS4A4A is expressed at the plasma membrane in monocytes but not in granulocytes or lymphocytes. In vitro differentiation of monocytes demonstrated that MS4A4A is expressed in immature but not activated dendritic cells, and in macrophages generated in the presence of interleukin‐4 ('alternatively activated' or M2 macrophages) but not by interferon‐γ and lipopolysaccharide ('classically' activated or M1 macrophages). MS4A4A was expressed in the U937 monocytic cell line only after differentiation. In normal bone marrow, MS4A4A was expressed in mature monocytes but was undetected, or detected at only a low level, in myeloid/monocytic precursors, as well as their malignant counterparts in patients with various subtypes of myeloid leukemia. Although MS4A4A was not expressed in healthy B lymphocytes, it was highly expressed in normal plasma cells, CD138+ cells from multiple myeloma patients, and bone marrow B cells from a patient with mantle cell lymphoma. These findings suggest immunotherapeutic potential for MS4A4A antibodies in targeting alternatively activated macrophages such as tumor‐associated macrophages, and in the treatment of multiple myeloma and mantle cell lymphoma.